Cardiovascular surgery in very low birth weight (≤1500 g) neonates. (5th December 2022) - Henmi, Soichiro; Essa, Yasin; Öztürk, Mahmut; Tongut, Aybala; Desai, Manan; Yerebakan, Can; d'Udekem, Yves
Abstract: OBJECTIVES: Low birth weight and prematurity are known risks of increased morbidity and mortality with undergoing cardiovascular surgery. Our aim was to review the outcomes of very low birth weight (≤1500 g) patients who have undergone cardiovascular surgery. METHODS: A retrospective review was performed for 32 very low birth weight (≤1500 g) patients who underwent cardiovascular surgery from 2004 to 2021 in our institution. RESULTS: Fifteen patients weighting ≤1500 g at surgery (≤1500-g group) were compared to 17 patients born with a weigh of ≤1500 g and weighting between 1500 and 2500 g at surgery (>1500- to ≤2500-g group) in this study. In-hospital mortality was 33% (5/15) in the ≤1500-g group and 24% (4/17) in the >1500- to ≤2500-g group ( P = 0.55). All patients with simple biventricular lesion survived following full repair. The occurrence of postoperative intracerebral haemorrhage was significantly higher in those operated at weight ≤1500 g than those weighting >1500 to ≤2500 g (40% vs 0%; P = 0.01). The 1- and 3-year survival rates were 66.0 ± 12.4% and 46.2 ± 14.8% in the ≤1500-g group and 76.5 ± 10.3% and 70.6 ± 11.1% in the >1500- to ≤2500-g group (log-rank P = 0.12). CONCLUSIONS: Cardiac surgery for a very low birth weight neonate resulted in a high early and late mortality. Early surgery is only acceptable for simple biventricular lesions if needed. Delayed surgery seems to provide better long-term outcomes in patients with complex lesions. Alternative strategies for neonatal cardiopulmonary bypass should be investigated in patients with complex biventricular and single ventricular lesions. Abstract : According to the World Health Organization, >1 in 10 pregnancies worldwide result in a premature birth, and these numbers are continuing to rise [1].